Determining the duration of the hadronic stage at RHIC-BES energies via resonance suppression using a full set of rate equations - Tim Neidig; Apiwit Kittiratpattana; Tom Reichert; Amine Chabane; Carsten Greiner; Marcus Bleicher (Physics Letters B)
We present realistic estimates for the duration of the hadronic stage in central Au+Au reactions in the RHIC-BES energy regime. To this aim, we employ a full set of coupled rate equations to describe the time evolution of the system from chemical to kinetic freeze-out. Combined with the recently measured data by the STAR collaboration on K⁎/K ratios, we show that the previous estimates substantially underestimated the duration of this stage due to the omission of the regeneration of hadron resonances. We provide an improved relation between the K⁎/K ratio at chemical and kinetic freeze-out and the life time of the hadronic phase. The calculated improved life times are now in line with estimates from other methods and are relevant for the NA61 and STAR collaborations and for upcoming experiments at the FAIR facility.